Upaya Meningkatkan Kemampuan Visual-Spasial Anak Usia Dini Melalui Pembelajaran Dengan Media Video dan Peta - Rusiyah, Rusiyah; Nurfaika, Nurfaika; Melo, Ramla Hartini (-, 2025)
Instilling a love for Indonesia’s homeland from an early age is essential. One effective approach to fostering patriotism is by introducing young children to Indonesia’s geography. Visual-spatial intelligence plays a crucial role in helping children comprehend spatial concepts and geographic locations. This program aims to enhance young children's visual-spatial intelligence through interactive learning methods utilizing video and map-based media. The activities include video presentations, map-based exercises, coloring maps of Indonesia, and identifying island names to promote active engagement in the learning process. The results indicate that 86.6% of children demonstrated high engagement during learning activities. Furthermore, 80% exhibited strong proficiency in map coloring, while another 80% successfully identified and named islands with high accuracy. These findings suggest that integrating video and map-based media effectively enhances children's geographical understanding and visual-spatial skills. The adoption of audiovisual and visual learning methods can be expanded in early childhood education to foster an interest in geography and strengthen visual-spatial intelligence from an early age.